Leprosy Specific Orofacial Aspects - Vathsala Naik; Raghavendra Kini; Smit Singla; Anjali Shetty (Wolters Kluwer Medknow Publications, 2011)
Leprosy is a chronic infection caused by Mycobactenum leprae, GHA- Hansen first identified the organism in 1873, so called Hansen disease. Mycobacterium leprae is a bacillus that presents a peculiar tropism for the skin and peripheral nerves. The upper airway has a great importance as a route of M. Leprae infection. The clinical spectrum of leprosy ranges from the tuberculoid form (TT) to the disseminative and progressive lepromatous form (LL). Cell-mediated immunity is considered to be the crucial defence against the disease and the magnitude of this immunity defines the extent of the disease- Facial lesions in leprosy can occur in all form of the disease and also in lepra reaction, oral lesions are rare but, when present, occur in the lepromatous form